Keunggulan Bersaing ; Faktor-Faktor yang Mempengaruhi Dan Dampaknya pada Kinerja Selling-In - Kadarningsih, Ana (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2013)
There is fenomenal gap that amount of Indosatâs outlets have increase 41,76% in year 2007 until 2008, but Net Profit Margin have decrease 18,66 % in year 2008. Also there is research gap that competitive advantage have influence on performance sales, other research result selling-in performance have influense on competitive advantage. The purpose of this research is to test the influences of outlet quality services, differentiation, company reputation, outlet quality relationship, environment adaptability, on competitive advantage to increase selling-in performance.The samples size of this research is 123 outlets of PT. Indosat. Using the Structural Equation Modeling (SEM) that be run with AMOS software , the results shows that the outlet quality services, differentiation, company reputation, outlet quality relationship, environment adaptability have influence on competitive advantage to increase selling-in performance.Keywords : Selling-in performance, competitive advantage.